PENGARUH PENGELOLAAN ASET TETAP TERHADAP PROFITABILITAS PERUSAHAAN MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2009-2011 - Maria .; Adieb Wijaksono (Universitas PGRI Palembang, 2013)
This research aims to determine the efficiency of fixed asset management in food and beverages entities listed on the Indonesia Stock Exchange also the significant influence between the rate of fixed assets turnover to the level of profitability on the food and beverages entities listed on Indonesia Stock Exchange. The population in this research is a food and beverages a total of 15 companys, the company sampled a total of 11 companies for 3 years from 2009-2011. Data used in this research is quantitative data and internal data. Data downloaded through the Indonesia Stock Exchange website is www.idx.co.id. Analysis techniques used are fixed asset efficiency analysis and simple linear regression analysis. The result of the analysis shows that the management of fixed assets of food and beverages entities listed on Indonesia Stock Exchange has been running efficiently and ther is a significant influencet between the rate of fixed asset turnover (FATO) and the rate of return on assets (ROA). Keywords : Fixed assets management, Fixed Assets Turnover (FATO), and Return Assets (ROA)